Development of Learning Media Assisted Adobeflash CS7 by Using the Demonstration Method in Science Learning - Riqqah Annisa Maharani; Yeni Erita; Darmansyah Darmansyah; Elfia Sukma (Postgraduate, University of Mataram, 2023)
The purpose of this project is to create an Adobe Flash CS7 application-assisted learning resource for science instruction in class IV of an elementary school. Development research was the method adopted in this study. The phrase